2023
DOI: 10.1021/acsami.3c01847
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrocatalytic Oxidation of Nitrogen to Nitric Acid Using Manganese Phthalocyanine

Abstract: Ammonia is produced through the energy-intensive Haber–Bosch process, which undergoes catalytic oxidation for the production of commercial nitric acid by the senescent Ostwald process. The two energy-intensive industrial processes demand for process sustainability. Hence, single-step electrocatalysis offers a promising approach toward a more environmentally friendly solution. Herein, we report a 10-electron pathway associated one-step electrochemical dinitrogen oxidation reaction (N2OR) to nitric acid by manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the XRD pattern, a peak is observed at ∼25 degrees (2 theta), confirming the formation of RGO for the (002) plane. In Figure a, two main diffraction peaks at 2 theta values of 6.91 and 9.12° are indexed to (100) and (1̅02), respectively (card no #02–063–3894), confirming the formation of β–MnPc. , A broad peak at ∼25 degrees (2 theta) was also observed, which indicates the formation of a 1:2 MnPc:RGO system. Different types of chemical bonds present in 1:2 MnPc:RGO were identified by Fourier transform infrared spectroscopy (FTIR) (Figures b and Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the XRD pattern, a peak is observed at ∼25 degrees (2 theta), confirming the formation of RGO for the (002) plane. In Figure a, two main diffraction peaks at 2 theta values of 6.91 and 9.12° are indexed to (100) and (1̅02), respectively (card no #02–063–3894), confirming the formation of β–MnPc. , A broad peak at ∼25 degrees (2 theta) was also observed, which indicates the formation of a 1:2 MnPc:RGO system. Different types of chemical bonds present in 1:2 MnPc:RGO were identified by Fourier transform infrared spectroscopy (FTIR) (Figures b and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The in-plane C–N and C–C stretching vibrations were assigned to 1200–1800 cm –1 . The peak at 1078 cm –1 corresponds to the C–N out-of-plane bending vibration in the MnPc:RGO system. , The UV–vis spectra of MnPc and the 1:2 MnPc:RGO electrocatalyst were analyzed in an ethanol medium. The UV–vis spectrum of MnPc:RGO showed (Figure S2) a characteristic B-band (Soret band) in the 353 nm region.…”
Section: Resultsmentioning
confidence: 99%
“…52,53 As exhibited in Figures 4g and S13−S14, the consecutive cycling experiment of Ru-HEP catalyst was carried out at 1.9 V (vs RHE), displaying a negligible fluctuation range of FE and NO 3 − yield rates in 15 consecutive cycles, suggesting its good stability. 54,55 XRD and XPS studies were further carried out for the Ru-HEP catalyst after the NOR test (Figures S15−S17), which indicated that the electronic structure and oxygenvacancy-site concentration of Ru-HEP presented negligible change after NOR catalysis, demonstrating that its oxygenvacancy-enriched structure was well maintained. These results confirmed that the increased oxygen-vacancy concentration of Ru-HEP derived from its high-entropy configuration can facilitate the activation and/or dissociation of N 2 , thus improving its NOR performance.…”
Section: Electrochemical Performance Evaluationmentioning
confidence: 99%
“…1–3 The industrially exemplary Haber-Bosch process, which is energy demanding and produces an extensive amount of greenhouse gases, is the primary method for the large scale industrial production of NH 3 . 4–6 A sustainable, environment-friendly, and energy efficient strategy for NH 3 synthesis is the desperate need of the hour. The production of NH 3 from N 2 via the nitrogen reduction reaction (NRR) has recently attracted an enormous amount of research interest.…”
Section: Introductionmentioning
confidence: 99%